2011
DOI: 10.1128/cmr.00033-10
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Potential and Molecular Epidemiology ofGiardiaSpecies and Giardiasis

Abstract: SUMMARY Molecular diagnostic tools have been used recently in assessing the taxonomy, zoonotic potential, and transmission of Giardia species and giardiasis in humans and animals. The results of these studies have firmly established giardiasis as a zoonotic disease, although host adaptation at the genotype and subtype levels has reduced the likelihood of zoonotic transmission. These studies have also identified variations in the distribution of Giardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

53
1,240
8
51

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,036 publications
(1,352 citation statements)
references
References 284 publications
(349 reference statements)
53
1,240
8
51
Order By: Relevance
“…Similar results were also obtained in this study concerning the prevalence of Giardia in sheep and cattle, which ranged in previous studies from 1.5% -38% in sheep and from 3.7% -57.8% in cattle. However, in the current study, among pigs the incidence of G. intestinalis infection was higher than previously described (up to 31.1%) [22,23,24,25]. In contrast, the prevalence of Giardia in dogs was lower than some data presented in literature where authors found the parasite in each studied dog [26,27].…”
Section: Discussioncontrasting
confidence: 82%
“…Similar results were also obtained in this study concerning the prevalence of Giardia in sheep and cattle, which ranged in previous studies from 1.5% -38% in sheep and from 3.7% -57.8% in cattle. However, in the current study, among pigs the incidence of G. intestinalis infection was higher than previously described (up to 31.1%) [22,23,24,25]. In contrast, the prevalence of Giardia in dogs was lower than some data presented in literature where authors found the parasite in each studied dog [26,27].…”
Section: Discussioncontrasting
confidence: 82%
“…Giardia intestinalis and Giardia lamblia), is a protozoan enteric parasite that causes acute, watery diarrhoea or giardiasis in 280 million people annually and is a common cause of waterborne outbreaks (Lane and Lloyd, 2002;Baldursson and Karanis, 2011;Painter et al 2015;Einarsson et al 2016). Most infections are selflimiting but chronic infections can lead to weight loss and malabsorption (Ryan and Cacciò, 2013) and infections are associated with stunting (low height for age), wasting (low weight for height) and cognitive impairment in children in developing countries (Berkman et al 2002;Feng and Xiao, 2011). Furthermore, acute giardiasis may disable patients for extended periods and can elicit protracted post-infectious syndromes, including irritable bowel syndrome and chronic fatigue (Hanevik et al 2014).…”
mentioning
confidence: 99%
“…The genus Cryptosporidium consists of 26 valid species and more than 50 genotypes with C. xiaoi, C. ubiquitum and C. parvum most frequently identified in sheep (Ryan et al, 2005;Santín et al, 2007;Soltane et al, 2007, Geurden et al, 2008, Mueller-Doblies et al, 2008, Quílez et al, 2008, Fayer and Santín, 2009Giles et al, 2009;Paoletti et al, 2009, Yang et al, 2009Díaz et al, 2010;Robertson et al, 2010;Wang et al, 2010;Fiuza et al, 2011;Shen et al, 2011;Sweeny et al, 2011;Sweeny et al, 2012a;Cacciò et al, 2013;Connelly et al, 2013;Imre et al, 2013;Yang et al, 2014a). Giardia duodenalis is the species infecting mammals and consists of eight major genetic groups (assemblages), two of which (A and B) are found in both humans and animals (including sheep) and are considered zoonotic, whereas the remaining six (C-H) are hostspecific and do not infect humans (Feng and Xiao, 2011;Ryan and Caccio, 2013). The most commonly reported genotypes in sheep are assemblage E (livestock genotype) and assemblage A (van Keulen et al, 2002;Lalle et al, 2005;Ryan et al, 2005;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…and Giardia spp. are gastro-intestinal protozoa that affect a wide range of mammals (Geurden et al, 2008;Feng and Xiao, 2011), including sheep. The prevalence of Cryptosporidium and Giardia in sheep varies between studies conducted worldwide but for Cryptosporidium generally ranges from 15%-27% in lambs (Santín et al, 2007;Robertson et al, 2010;Ye et al, 2013;Yang et al, 2014a) and for Giardia generally ranges from 1.5-55.6% (Feng and Xiao, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation